Anemia in Pregnancy: Screening and Clinical Management Strategies. Issue 1 (January 2022) - Stanley, Angela Y.; Wallace, Jerrol B.; Hernandez, Andrea M.; Spell, Jenna L.
Abstract : Abstract: Screening recommendations for anemia during pregnancy, etiologies of inherited and noninherited forms of anemia, their impact on maternal–fetal outcomes, and the clinical management of pregnant patients presenting with these conditions are reviewed. Anemia during pregnancy can cause adverse perinatal outcomes including preterm labor, premature rupture of membranes, and increased maternal and fetal mortality. Physiologic (dilutional) anemia and iron deficiency anemia are the two most common noninherited forms of anemia, and some cases may be the result of an underlying comorbidity such as diabetes or lupus. Aplastic anemia and autoimmune hemolytic anemia are uncommon forms of noninherited anemias that also merit discussion. Inherited forms of anemia include sickle cell disease, alpha-thalassemia, and beta-thalassemia. Timely diagnosis and treatment of anemia during pregnancy, whether inherited or noninherited, is imperative to protect mother and baby from potential adverse outcomes associated with these conditions. Abstract : Anemia during pregnancy can lead to adverse maternal and newborn outcomes. Current recommendations for screening and treatment of anemia during pregnancy are covered in detail with guidance for incorporating them into clinical practice.